Hedgehog - Leach, Michael (New York : PowerKids Press, 2009)
Presents an illustrated discussion of hedgehogs, covering their physical characteristics, habitat, food, predators, mating habits, and life cycle, and offers information on how to find signs of their activity.
Includes bibliographical references (p. 31) and index.
5.8
K-3
Keywords: Hedgehogs -- Juvenile literature; Hedgehogs; Hedgehogs; Hedgehogs